232k views
13 votes
Write step by step pls
1/2r−3=3(4−3/2r)

User Odrade
by
5.2k points

1 Answer

6 votes

Answer:

r = 3

Explanation:


(r)/(2) - 3 = 3(4 - (3r)/(2) )

The first step to solve for "r" is to simplify the distributive property on the RHS. To simplify the distributive property, we need to multiply the term outside the parenthesis with the terms inside the parenthesis.


\rightarrow (r)/(2) - 3 = 12 - (9r)/(2)

Now, add 9r/2 and 3 both sides to isolate the constants and variables.


\rightarrow (r)/(2) + (9r)/(2) = 12 + 3

Simplify both sides.


\rightarrow (10r)/(2)= 12 + 3


\rightarrow 5r = 15

Divide 5 both sides.


\rightarrow \boxed{r = (15)/(5) = 3}

User Mikel Sanchez
by
5.3k points